PERAN ORANG TUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP ISLAM ANNURIYAH MALANG - Lita Ainun Qolbi; Imam Syafi'i; Lia Nur Atiqoh Bela Dina (VICRATINA, 2022)
In the day and age parents who send their children to school assume that is theteacher’s job to take full responsibility for ensuring the success of their children it isnot justified because no mather how busy the situation is, parents stil play a role inpaying attention to student learning success. There are some parents who understandthe importance of studying religious knowledge, so parents take the intiative to sendtheir children to school by deepening their religious knowledge. It is also the same withthe Annuriyah Islamic Junior High School which is located in the Islamic boardingschool even though the children are far from their parents but the role of parents isstill needed in the success of student learning. Therefore the role of parents in payingattention to student learning outcomes greatly affects student’s learning moreenthusiastically.